Use of Intracardiac Echocardiography in Interventional Cardiology: Working With the Anatomy Rather Than Fighting It. Issue 21 (22nd May 2018) - Enriquez, Andres; Saenz, Luis C.; Rosso, Raphael; Silvestry, Frank E.; Callans, David; Marchlinski, Francis E.; Garcia, Fermin
Abstract : The indications for catheter-based structural and electrophysiological procedures have recently expanded to more complex scenarios, in which an accurate definition of the variable individual cardiac anatomy is key to obtain optimal results. Intracardiac echocardiography (ICE) is a unique imaging modality able to provide high-resolution real-time visualization of cardiac structures, continuous monitoring of catheter location within the heart, and early recognition of procedural complications, such as pericardial effusion or thrombus formation. Additional benefits are excellent patient tolerance, reduction of fluoroscopy time, and lack of need for general anesthesia or a second operator. For these reasons, ICE has largely replaced transesophageal echocardiography as ideal imaging modality for guiding certain procedures, such as atrial septal defect closure and catheter ablation of cardiac arrhythmias, and has an emerging role in others, including mitral valvuloplasty, transcatheter aortic valve replacement, and left atrial appendage closure. In electrophysiology procedures, ICE allows integration of real-time images with electroanatomic maps; it has a role in assessment of arrhythmogenic substrate, and it is particularly useful for mapping structures that are not visualized by fluoroscopy, such as the interatrial or interventricular septum, papillary muscles, and intracavitary muscular ridges. Most recently, a three-dimensional (3D) volumetric ICE system has also been developed, with potential for greater anatomic information and a promising role in structural interventions. In this state-of-the-art review, we provide guidance on how to conduct a comprehensive ICE survey and summarize the main applications of ICE in a variety of structural and electrophysiology procedures. Abstract : Supplemental Digital Content is available in the text.